2018
DOI: 10.3389/fchem.2018.00078
|View full text |Cite
|
Sign up to set email alerts
|

N/S Co-doped Carbon Derived From Cotton as High Performance Anode Materials for Lithium Ion Batteries

Abstract: Highly porous carbon with large surface areas is prepared using cotton as carbon sources which derived from discard cotton balls. Subsequently, the sulfur-nitrogen co-doped carbon was obtained by heat treatment the carbon in presence of thiourea and evaluated as Lithium-ion batteries anode. Benefiting from the S, N co-doping, the obtained S, N co-doped carbon exhibits excellent electrochemical performance. As a result, the as-prepared S, N co-doped carbon can deliver a high reversible capacity of 1,101.1 mA h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…As shown in Figure 4a, the first discharge and charge capacities of the N/S-CS are 396 mA h g −1 , and 233 mA h g −1 , respectively, corresponding to an initial coulombic efficiency of 58.7%. The large irreversible capacity loss can be ascribed to the inevitable formation of a solid electrolyte interphase (SEI) layer on the relatively large specific surface area and decomposition of electrolytes, which are common to most anode materials [37,38]. The presence of a sloping plateau at around 0.9 V in the first cycle can be attributed to the formation of SEI films [38], which agrees well with the CV results.…”
Section: Resultssupporting
confidence: 70%
“…As shown in Figure 4a, the first discharge and charge capacities of the N/S-CS are 396 mA h g −1 , and 233 mA h g −1 , respectively, corresponding to an initial coulombic efficiency of 58.7%. The large irreversible capacity loss can be ascribed to the inevitable formation of a solid electrolyte interphase (SEI) layer on the relatively large specific surface area and decomposition of electrolytes, which are common to most anode materials [37,38]. The presence of a sloping plateau at around 0.9 V in the first cycle can be attributed to the formation of SEI films [38], which agrees well with the CV results.…”
Section: Resultssupporting
confidence: 70%
“…In galvanostatic charge/discharge test (Figures 4D,E ), the charge capacity of AAC attractively reaches 479.2 mAh g −1 after 150 cycles at a current density of 0.5 A g −1 with 96% retention. Furthermore, it can achieve reversible capacity of 691.7 mAh g −1 after 1200 cycles at a high rate of 2 A g −1 with an ascending tendency in the first few hundred cycles, which is stemmed from gradual electrochemical activation of AAC and is similar to most carbonaceous anode materials (Qie et al, 2012 ; Lv et al, 2015 ; Xiong et al, 2018 ; Yang et al, 2018 ; Zhang et al, 2018b ). On the contrary, ordinary AC merely delivers 261.6 mAh g −1 at 0.5 A g −1 and 229.1 mAh g −1 at 2 A g −1 under the same cycling condition.…”
Section: Resultsmentioning
confidence: 97%
“…Amorphous carbon, compared to graphite, can reach higher specific capacity with enlarged interlayer distance and shortened ion transportation paths. Owing to environment amiability, sustainability and cost efficiency, ta large amount of diverse selectable biomass materials, such as protein (Li et al, 2013 ), peanut shell (Lv et al, 2015 ), bee pollen grain (Tang et al, 2016 ), rice husk (Zhang et al, 2016a ), cotton (Li et al, 2016 ; Xiong et al, 2018 ; Yang et al, 2018 ), garlic skin (Zhang et al, 2018c ), have been investigated in depth of their electrochemical capabilities. Generally, biomass-derived amorphous carbon can be synthesized by directly pyrolysis (Li et al, 2016 ) − (Wang et al, 2015 ) or hydrothermal treatment (Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three C atoms around a mono-vacancy defect were substituted with different numbers of atomic N and/or S dopants. Regarding model structures in this investigation, research groups successfully reported the synthesis of N- and S-doped graphene [ 22 , 43 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. In order to analyze the effects of the N and S doping levels on electronic properties, we first fixed the doping concentration to three dopant atoms at the mono-vacancy defect.…”
Section: Resultsmentioning
confidence: 99%